2018
DOI: 10.1200/jco.2018.36.6_suppl.296
|View full text |Cite
|
Sign up to set email alerts
|

Real-world study of enzalutamide and abiraterone acetate (with prednisone) tolerability (REAAcT): Results.

Abstract: 296 Background: Enzalutamide (E) and abiraterone acetate with prednisone (AAP) are approved for treatment (tx) of metastatic castration resistant prostate cancer (mCRPC). Concerns of differences in CNS manifestations and tolerability between E and AAP have been reported. REAAcT evaluated tolerability in patients (pts) newly starting E and AAP for mCRPC. Methods: This was a multicenter, Phase IV, non-randomized, prospective real-world study (NCT02663193). The tx (E or AAP) determined by the treating physician … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 0 publications
0
14
0
Order By: Relevance
“…Two articles reported the risk for total CNS events. 15,24 Pilon et al. 15 reported that the rate of total CNS events was 7.3% with AA versus 9.1% with EnZ, and Shore et al.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Two articles reported the risk for total CNS events. 15,24 Pilon et al. 15 reported that the rate of total CNS events was 7.3% with AA versus 9.1% with EnZ, and Shore et al.…”
Section: Resultsmentioning
confidence: 99%
“…Fourteen studies involving 3469 participants were included in the meta-analysis. 1225 The characteristics of the eligible studies are presented in Table 1. The clinical outcomes of included studies are presented in Appendix 1.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations